Isolation and characterization of novel broad host range bacteriophages of Vibrio cholerae O1 from Bengal - Sarkar, BanwarilalL; Sarkar, Sounak; Das, Mayukh; Bhowmick, TusharSuvra; Koley, Hemanta; Atterbury, Robert; Chakrabarti, AlokK (Medknow Publications, 2018)
Objectives: We have isolated a total of five newer cholera phages which are novel broad host range to incorporate with the existing phage typing schemes for an extended typing scheme. Materials and Methods: These newly isolated phages were well characterized including the electron micrograph. A total of 300 Vibrio cholerae strains were isolated from the different endemic region in India were included in phage typing study. Results: These phages were found different from the existing phages. Electron microscopic results showed that the phages belonged to myophage and podophage group. Characterization of the phages based on pH, temperature, and organic solvent sensitivity showed differences among the phages used in this study. All the strains of Vibrio O1 were typeable (100%) with the five set of cholera phages. Of these, 40% strains were clustered under Type-1. Conclusion: The newer Vibrio phages are novel and broad host range and will be useful to incorporate with the existing phage typing system for more precisely discriminate the strains of Vibrio cholerae.